A case of adult cannibalism in BALB/c mice and the effect of Eucalyptus oil as a treatment (Journal of Laboratory Animal Science, 2024)
Eight-week-old male and female BALB/c mice that were procured and kept for quarantine experienced 10% mortality in  males and 3.3% in females from the second day onwards with partially mutilated carcasses in both cages. Considering  the stress due to travel Vitamin C was provided in the drinking water from day 4. The percentage of  mortality was reduced as compared to the first day however mortality continued to 5th day. Furthermore, the  application of eucalyptus oil in the cage and animal body surface of the animals for one week repeatedly  results in a substantial decrease in % mortality in male and female mice.
Keywords: Adult BALB/c mice; cannibalism; Eucalyptus oil; vitamin-C